2016
DOI: 10.1016/j.rmed.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Ambrisentan response in connective tissue disease-associated pulmonary arterial hypertension (CTD-PAH) – A subgroup analysis of the ARIES-E clinical trial

Abstract: ABSTRACT:Objective: Pulmonary arterial hypertension (PAH) is a condition which may lead to right ventricular failure and early mortality and is an important complication in patients with connective tissue disease (CTD). Previously, the endothelin A selective receptor antagonist, ambrisentan, has demonstrated efficacy and safety in treating patients with PAH due to a WHO Group I etiology. In this report, we describe the 3-year efficacy and safety of ambrisentan in patients with CTD associated PAH (CTD-PAH). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Two large RCTs (ARIES 1 and 2) assessed the efficacy and safety of ambrisentan (2.5, 5, and 10 mg daily) in PAH. 38 Fischer et al 39 performed a subanalysis in patients with CTD-PAH (n ¼ 124) based on a combination of these trials (ARIES-C) and their open-label extensions (ARIES-E). The primary endpoint for both studies was change in 6MWT from baseline to week 12 compared to placebo.…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 99%
“…Two large RCTs (ARIES 1 and 2) assessed the efficacy and safety of ambrisentan (2.5, 5, and 10 mg daily) in PAH. 38 Fischer et al 39 performed a subanalysis in patients with CTD-PAH (n ¼ 124) based on a combination of these trials (ARIES-C) and their open-label extensions (ARIES-E). The primary endpoint for both studies was change in 6MWT from baseline to week 12 compared to placebo.…”
Section: Endothelin Receptor Antagonistsmentioning
confidence: 99%
“…Therapies have progressed from a time when only intravenous epoprostenol was available [144,145] and outcomes were very poor, to the current availability of multiple licensed treatments that can be used in combination ( Table 2). The early studies that led to the licensing of various PAH therapies, including bosentan and sildenafil, focused on short term gains in exercise capacity; in these studies, the response of patients with SSc-associated PAH or CTD-associated PAH was often less efficacious than patients with other forms of PAH, although most treatments seem to result in meaningful benefit in the majority of patients with SSc-associated PAH [146,147,148,149]. However, evidence in clinical practice suggests that these therapies have long-term benefits in SSc-associated PAH [142], which is supported by key eventdriven clinical trials published in the past 3 years [150,151,152]: the SERAPHIN trial (which tested the oral endothelin receptor antagonist macitentan), the GRIPHON trial (which tested the prostcyclinreceptor agonist selexipag) and the AMBITION trial (which tested a combination therapy of ambrisentan (endothelin receptor antagonist) and tadalafil (a PDE5 inhibitor)).…”
Section: [H2] Treatment Approaches For Lung Fibrosismentioning
confidence: 99%
“…3 From included studies in F I G U R E 4 Forest plot comparing Combination vs Monotherapy A, 6 min walk distance; B, clinical failure endpoint our analysis, the pattern of frequency of AEs appears similar to that of the idiopathic subtype. 3,31 Vasodilatory AEs, such as peripheral edema, were more common with initial combination therapy compared to monotherapy. 3 Choosing…”
Section: Discussionmentioning
confidence: 99%
“…However, CTD-specific data from 3 of these studies were reported in 3 subsequent publications. 3,30,31 The final analysis included a total of 3100 PAH patients, of whom 784 belonged to the CTD-PAH subgroup (25.3%). Characteristics of the included studies are summarized in Table 1 Five studies compared various forms of combination therapy to monotherapy.…”
Section: Study Characteristicsmentioning
confidence: 99%